Pengaruh Investasi, Tenaga Kerja dan Pertumbuhan Penduduk Terhadap Pertumbuhan Ekonomi di Kabupaten Pelalawan - Windy Ayu Astuti; Muhammad Hidayat; Ranti Darwin (Akuntansi & Ekonomika, 2017)
This study aims to determine the effect of investment, labor and population growth on economic growth in Pelalawan Regency in 2006-2015. This type of research is descriptive quantitative. The use of secondary data from the publication of Central Bureau of Statistics Pelalawan District in the form of time series data that is Economic Growth, Investment (PMA & PMDN), Labor and Population Growth. The result of the research shows that from t-test result can be concluded for each variable of investment and population growth have significant effect to economic growth, while labor does not have significant effect to economic growth in Pelalawan Regency. The result of determination coefficient test (R2) shows that the ability of independent variable (investment, labor, and population growth) in explaining the dependent variable (economic growth) is 94.82 percent while the remaining 5.18 percent is explained by other variables outside the model.